Construction and implementation of Traditional Chinese Medicine nursing outpatient clinic (中医护理门诊的建设与实施方法) - MIAO Yuxin (苗玉鑫); SUN Yanrong (孙艳荣) (Association of Integrative Nursing, 2022)
The aim of this paper was to share the construction and implementation experience of the green nursing outpatient clinic of Traditional Chinese Medicine (TCM). The TCM nursing outpatient clinic mainly provides appropriate TCM technology, establishes personalized TCM health management archives, carries out health promotion, and improves patient satisfaction. The implementation of nursing clinic meets the diversified needs of patients and improves the level of nursing service and traditional Chinese medicine nursing. (本文探讨了中医护理门诊的建设及实施方法。中医护理门诊主要为患者实施中医适宜技术, 建立个性化中医健康管理档案, 开展健康促进工作, 提高患者满意度。中医护理门诊的建设与实施满足了患者多元化的需求, 有助于提高护理服务质量及中医护理水平。)